Spatiotemporal regulation of ventilator lung injury resolution by TGF-β1+ regulatory B cells via macrophage vesicle-nanotherapeutics - Jing, Ren; Liao, Xiaoting; Mo, Jianlan; He, Sheng; Xie, Xianlong; Hu, Zhaokun; Pan, Linghui (Frontiers in Immunology, 2025)
BackgroundRegulatory B cells (Breg) critically orchestrate inflammatory resolution and tissue repair. This study investigates the therapeutic potential of transforming growth factor (TGF)-β1-producing Bregs in ventilator-induced lung injury (VILI), leveraging biomimetic nanotechnology to overcome limitations of conventional cytokine delivery.MethodsWe engineered macrophage-derived microvesicle-encapsulated nanoparticles (TMNP) for pH-responsive, spatiotemporally controlled TGF-β1 release. Therapeutic efficacy was evaluated in a murine VILI model through longitudinal immunophenotyping, histopathology, and cytokine profiling at post-ventilation days 1 and 10 (PV1d, PV10d).ResultsVILI triggered biphasic pulmonary Breg expansion (PV1d: 7.83-fold vs. controls, P < 0.001; PV10d resurgence) coinciding with peak injury. TMNP administration induced sustained TGF-β1 bioavailability (PV10d: 3.6-fold vs. free cytokine, P < 0.001), attenuating histopathology (22.5% reduction in alveolar hemorrhage, P < 0.01) and suppressing IL-6/TNF-α (P < 0.01). Treatment concomitantly expanded Breg populations and modulated T cell subset.ConclusionTMNP orchestrates Breg-mediated immunoresolution through precision cytokine delivery and lymphocyte modulation, enabling dual-phase protection against ventilation-associated immunopathology. This paradigm represents a transformative approach for acute respiratory distress management.